Associated Factors of Undernutrition among Lactating Mothers: Literature Review - Aprilya Roza Werdani (Fakultas Kedokteran, Universitas Papua, 2024)
Lactating mothers in low and middle-income countries including Ethiopia and Uganda are vulnerable to undernutrition. Undernutrition during lactation increases the risk of disease among mothers and children. This study aimed to review the prevalence and factors associated with undernutrition among lactating mothers. We used literature from several electronic databases including BioMed Central, Pubmed, SpringerPlus, Wiley Online Library, Google Scholar, and Taylor & Francis to collect relevant literature about the prevalence and associated factors of undernutrition among lactating mothers. Of the eight studies, the lowest prevalence of undernutrition among lactating mothers was 8.2% and the highest was 54.8%, and most of them (6 of 8 studies) showed a prevalence of undernutrition above 20%. Many factors are associated with undernutrition among lactation mothers, including household food security, food diversity, not using additional food, meal frequency, place of delivery, nutrition education, potable water source, latrine facilities, birth spacing, family income, and maternal age, education, and maternal working status. The prevalence of undernutrition among lactating mothers is still high. Inadequate access to food and health services, poor environment, and low family socio-economic factors were associated factors of undernutrition among lactation mothers